2019
DOI: 10.1039/c8sc03778g
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the biosynthetic pathway to agnestins A and B reveals the reductive route to chrysophanol in fungi

Abstract: Identification of a reductase (AgnL4) confirms that in vivo anthraquinone to anthrol conversion is an essential first step in aromatic deoxygenation of anthraquinones catalysed by AgnL6 (reductase) and AgnL8 (dehydratase).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 38 publications
(32 reference statements)
5
72
0
Order By: Relevance
“…The two-step pathway described here explains the significant structural changes that must occur to transform the almost flat fasamycin skeleton into the twisted chair-like configuration of the formicamycins. The dearomatization of aromatic systems as a prelude to structural diversification has been described for several natural products including, for example, recent mutational analysis of the agnestins 19 and cryptosporioptides 20 where deletion of genes encoding putative Baeyer–Villigerases led to accumulation of the anticipated aromatic precursors. For the Baeyer–Villiger activity of ForX, two alternative mechanisms can be invoked for reaction between the fasamycin substrate, reduced flavin cofactor and oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-step pathway described here explains the significant structural changes that must occur to transform the almost flat fasamycin skeleton into the twisted chair-like configuration of the formicamycins. The dearomatization of aromatic systems as a prelude to structural diversification has been described for several natural products including, for example, recent mutational analysis of the agnestins 19 and cryptosporioptides 20 where deletion of genes encoding putative Baeyer–Villigerases led to accumulation of the anticipated aromatic precursors. For the Baeyer–Villiger activity of ForX, two alternative mechanisms can be invoked for reaction between the fasamycin substrate, reduced flavin cofactor and oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical skeletons of fasamycins(1)(2)(3) and formicamycins (4-16) isolated from S. formicae KY5, and Baeyer-Villiger lactone intermediates(17)(18)(19)(20)(21) isolated from the S. formicae DforY mutant in this study (for detailed substituent variations including halogenation or Omethylation, seeFig. S1 †).…”
mentioning
confidence: 99%
“…7 This kind of metabolites showed numerous pharmacological activities such as anti-cancer, 8 antioxidant, 9 diuresis and saluresis, 10 hepatoprotective, 11 anti-gout, 12 anti-inflammatory, 13 anti-diabetes, 14 and gastroprotective. 15 Recently, these xanthones easily incorporated into micro-molecules attributing to intriguing biological activities had drew attention from phytochemical, 16 organic synthesis, 17,18 and pharmacological endeavors. 19 Xanthones from the genus Garcinia had structural diversity and exhibited significant biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic studies using antiSMASH24 identified ten BGCs containing non-reducing polyketide synthase (nr-PKS) genes. A putative gene cluster for xanthone biosynthesis25 was readily identified by BLAST analysis using protein sequences from: the shamixanthone 3 /monodictyphenone 4 BGC from Aspergillus nidulans ;5,6,26 the agnestin 6 BGC from Paecilomyces variotii ;8 the recently (but partially, vide infra ) described secalonic acid 10 BGC from Claviceps purpurea ;27 the geodin 5 BGC from Aspergillus terreus ;7 and the cladofulvin 7 BGC from Cladosporium fulvum 9. Development of a transformation system, targetted knockout of the putative cryptosporioptide ( dmx ) PKS using the bipartite method of Neilsen and coworkers,28 and subsequent observation of abolition of all cryptosporioptide production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Emodin 1 is a precursor of the antifungal agent geodin 5 ,7 which while not strictly a xanthone, belongs to the same biosynthetic family. We have also recently isolated other xanthones such as agnestin A 6 from Paecilomyces variotii and linked it to its biosynthetic genes 8. Cladofulvin 7 9 from the tomato pathogen Cladosporium fulvum is a dimeric anthraquinone also derived from 2 .…”
Section: Introductionmentioning
confidence: 99%